PENGARUH KEPEMIMPINAN SITUASIONAL KEPALA SEKOLAH, LINGKUNGAN KERJA, DAN MOTIVASI BERPRESTASI, TERHADAP KINERJA GURU SMK - Asmawi, Asmawi; Wahyudi, Wahyudi; Chiar, H.M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract  The aim of this research is to find out the influence of situational leadership of headmasters, working environments, and prestige motivation upon teachers?s performance of the state vocational high school of Sintang Regency, partially or altogether. He uses qualitative approach with ex post facto design. He applies his reseach on seven Vocational High Schools on Sintang Regency, they are SMKN 1 Sintang, SMKN 1 Dedai, SMKN 1Sepauk, SMKN 1 Kelam Permai, SMKN 1 Kayan Hilir, SMKN 1 Ketungau Tengah, SMKN 1 Serawai. He has 136 teachers as samples. He uses Proportionate Stratified Random Sampling. He finds out that firstly: Situational leadership of headmasters has no significant influence upon teachers?s performance of the state vocational high school of Sintang regency with 0,069>0,05significant value. Secondly, working environments has significant influence upon teachers?s performance of the state vocational high school of Sintang regency with 0,001<0.005 significant value. Third, Prestige motivation has significant influence upon teachers?s performance of the state vocational high school of Sintang regency with 0.000<0.05 significant value. Fourth, Situational leadership of headmasters has no significant influence upon prestige motivation of the state vocational high school of Sintang regency with 0.257 > 0.05 significant value. Key Words: Leadership, Motivation, Working Environments, Performance